MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS III MELALUIPENERAPAN METODE PEMBELAJARAN EXAMPLES NON EXAMPLESDI SDN 010 BAYAS JAYA - Masdar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This research was a classroom action research aiming to improve students' learning outcomes and speaking skills through the Examples Non Examples method. This research was conducted at grade III of SDN 010 Bayas Jaya, Indragiri Hulu. The subjects in this research were 28 third-grade students of SDN 010 Bayas Jaya. The research results obtained that the percentage of students' speaking skills after implementing the Example Non-Example method in the second cycle was 86.75% or classified as "very good" because it was in the range of 80%- 100%. Thus, in the second cycle, the students' speaking skills were said to be improved or better because they reached the KKM of 70. Moreover, implementing the Example NonExample method increased the students' learning activity. Finally, this research found progressin the students' speaking skills at grade III of SDN 010. Bayas Jaya Indragiri Hilir.